Biodegradation and possible source of Silurian and Carboniferous reservoir bitumens from the Halahatang sub-depression, Tarim Basin, NW China. (December 2016) - Cheng, Bin; Wang, T.-G.; Chen, Zhonghong; Chang, Xiangchun; Yang, Fulin
Abstract: Five core samples comprising three Silurian and two Carboniferous bituminous sandstones from the Halahatang sub-depression (Tarim Basin, NW China) were studied to determine the nature and extent of microbial alteration and possible source(s) of the reservoir bitumens. A total of twelve Ordovician crude oil samples from this sub-depression were also examined for comparative purposes. Co-occurrence of a series of 25-norhopanes (NHs) (C28 –C34 ), variable amounts of chromatographically unresolved complex mixture (UCM), and diminished concentrations of n -alkanes below ca. C20 in saturated hydrocarbon fractions of the Silurian and Carboniferous bitumens indicates that they are mixtures of heavily biodegraded oil from a former charge and slightly biodegraded oil from a later charge. The presence of C28 –C34 25-NHs suggests a biodegradation level of at least PM 6 for these bitumen samples. Nevertheless, minor differences in terpane and sterane distributions between the Silurian and Carboniferous bitumen samples were observed which can be attributed to small variations in biodegradation levels. Values for the 25-NH ratio (Peters et al., 1996), gammacerane/(gammacerane + C30 hopane), C28 25-NH/C29 hopane and C29 25-NH/C30 hopane ratios indicate slightly higher levels of microbial alteration for the Silurian bitumens compared to the Carboniferous bitumens, although caution must be exercised when comparing the biodegradation intensities using molecular parameters. The Ordovician crude oil samples appear to be more severely biodegraded than the Silurian and Carboniferous bitumens, as evidenced by higher concentrations of tricyclic terpanes relative to hopanes, and pregnanes and diasteranes relative to the regular steranes, although thermal maturity effects cannot be ruled out. Geochemical correlation studies were successfully applied based on carbon isotopes and biomarkers including tricyclic terpanes and triaromatic steroids which are highly resistant to severe biodegradation (PM 6). Bulk isotopic compositions, distribution patterns and certain ratios of these biomarkers indicate that the Ordovician crude oils and the Silurian and Carboniferous bitumens originated from a single source. They were probably derived from Middle–Upper Ordovician source rocks. Highlights: Geochemical characteristics of Silurian and Carboniferous bitumens from the Halahatang sub-depression have been described. Minor differences in biodegradation levels between the Silurian and Carboniferous bitumens have been evaluated. Possible source for the Silurian and Carboniferous bitumens has been discussed.